Gendered Linguistic Analysis of Jane Austen's 'Emma': Unveiling Feminist Perspectives at the Word Level - Br Pane, Khairina Juliana; Lubis, Syahron; Rangkuti, Rahmadsyah; Br Perangin – Angin, Alemina (Universitas Islam Sultan Agung, 2024)
This research aims to analyze the stylistic and linguistic selection in representing women in Jane Austen’s novel entitled Emma by emphasizing the gender specific words presented in the novel and discover the gender specific theme exposed in the novel. This research conducts a qualitative analysis to explore the stylistic and linguistic choices employed in depicting women in Jane Austen's novel,